Noncrystallizable Charge‐Transporting Hosts for Phosphorescent Organic Light Emitting Diodes: Decreased Emitter Aggregation. Issue 4 (31st January 2020) - Chakraborty, Rajarshi; Molaire, Michel F.; Weiss, David S.; Pecorella, Joseph N.; Clark, Daniel A.; Rothberg, Lewis J.; Zeng, Honzhi; Yu, Tianhao
Abstract : Organic light emitting diodes (OLEDs) with phosphorescent emitters (PhOLEDs) exhibit efficiency roll‐off at high luminance because the long‐lived triplet excitons are prone to emission quenching and triplet–triplet annihilation (TTA). Herein, the synthesis, purification, and characterization of an emitter layer host that is a noncrystallizable mixture of isomers (OLEDIQ HT‐1700) is described. In this host, the triplet lifetime of a phosphorescent yellow emitter (IYD‐560) is increased relative to a conventional single‐molecule host (3, 3′‐di(9H‐carbazol‐9‐yl)‐1, 1′‐biphenyl, mCBP), with high photoluminescence quantum yields and unchanged emission spectra. Characterization of the doped films with differential scanning calorimetry (DSC) and microscopy showed that the emitter is incompatible in mCBP but totally compatible with the noncrystalline host. The increased triplet lifetime is interpreted as decreased triplet quenching in the noncrystallizable host‐based film, while emitter aggregation in the conventional host film leads to triplet quenching. Abstract : Phosphorescent organic light emitting diodes (OLEDs) with the single‐molecule charge‐transporting host, 3, 3′‐di(9H‐carbazol‐9‐yl)‐1, 1′‐biphenyl (mCBP), exhibit degraded performance at high brightness due to emitter aggregation. A noncrystallizable host, OLEDIQ HT‐1700, is physically compatible with a phosphorescent emitter whereas mCBP is incompatible. The phosphorescent lifetime of the emitter is longer in HT‐1700. Noncrystallizable emitter layer hosts can prevent emitter aggregation.